Hydrophilic scaffolds of oxime as the potent catalytic inactivator of reactive organophosphate. (5th January 2019) - Tang, Shengzhuang; Wong, Pamela T.; Cannon, Jayme; Yang, Kelly; Bowden, Sierra; Bhattacharjee, Somnath; O'Konek, Jessica J.; Choi, Seok Ki
Abstract: Despite its efficacy as a skin decontaminant of reactive organophosphates (OP), Dekon 139—a potassium salt of 2, 3-butanedione monooxime (DAM)—is associated with adverse events related to percutaneous absorption largely due to its small size and lipophilicity. In order to address this physicochemical issue, we synthesized and evaluated the activity of a focused library of 14 hydrophilic oxime compounds, each designed with either a DAM or monoisonitrosoacetone (MINA) oxime tethered to a polar or charged scaffold in order to optimize the size, hydrophilicity, and oxime acidity. High-throughput colorimetric assays were performed with paraoxon (POX) as a model OP to determine the kinetics of POX inactivation by these compounds under various pH and temperature conditions. This primary screening led to the identification of 6 lead compounds, predominantly in the MINA series, which displayed superb catalytic activity by reducing the POX half-life ( t 1/2 ) by 2–3 fold relative to Dekon 139. Our mechanistic studies show that POX inactivation by the oxime compounds occurred faster at a higher temperature and in a pH-dependent manner in which the negatively charged oximate species is ≥ 10–fold more effective than the neutral oxime species. Lastly, using one of the lead compounds, we demonstrated its promising efficacy for POX decontamination in porcine skin ex vivo, and showed its potent ability to protect acetylcholine esterase (AChE) through POX inactivation. In summary, we report the rational design and chemical biological validation of novel hydrophilic oximes which address an unmet need in therapeutic OP decontamination. Graphical abstract: Highlights: Physicochemical design of hydrophilic oximes for organophosphate decontamination. Identification of oximes that display shorter paraoxon half-life than Dekon 139. Rate of paraoxon inactivation determined by oxime reactivity, pH and temperature. A lead oxime demonstrated for effective paraoxon decontamination in porcine skin. Paraoxon inactivation led to protection of acetylcholine esterase in vitro .